THE RELATIONSHIP BETWEEN SATISFACTION WITH LIFE AND EMPLOYEE ENGAGEMENT - Anton Vorina (Journal of Process Management. New Technologies, 2013)
Modern organizations need dedicated employees who are engaged with their work. The theme of employee engagement has generated a great deal of attention among many human resource practitioners and academic researchers across the world. In this paper we present an analysis the relationship between satisfaction with life and employee engagement in a casual sample of 1006 respondents in Slovenia. Based on multipla linear regression analysis, we found that relation between satisfaction with life and employee engagement is statistically significant (F: 381.80, Sig.: 0.000). Among two evaluated multiple regression models, as the most appropriate, the multiple linear regression model with one regressors (satisfaction with life) and sample size of 1006. We found out that the engagement of employee would increase if the satisfaction with life increase.